Late Cenozoic faulting and the stress state in the south-eastern segment of the Siberian platform - V. A. Sankov; A. V. Parfeevets; A. I. Miroshnichenko; L. M. Byzov; M. A. Lebedeva; A. V. Sankov; А. А. Dobrynina; S. N. Kovalenko (Геодинамика и тектонофизика)
We have studied the structural geology and geomorphology of the fault zones in the junction area of the Angara-Lena uplift and the Predbaikalsky trough. We have analyzed faults and folds and reconstructed paleostresses for this junction area named the Irkutsk amphitheatre. Our study shows that syn-fold (Middle Paleozoic) faults include thrusts, reverse faults and strike-slip faults with reverse components, that occurred due to compression from the neighbouring folded region. Recently, contrary to compression, faulting took place under the conditions of extension of the sedimentary cover: most of these recent faults have been classified as normal faults. In the Late Cenozoic, the platform cover was subjected to brittle and partly plicative deformation due to the NW–SE-trending extension that is most clearly observed in the adjacent Baikal rift. Thus, the divergent boundary between the Siberian block of the North Eurasian plate and the Transbaikalia block of the Amur plate is a zone of dynamic influence, which occupies the area considerably exceeding the mountainous region on the Siberian platform. Important factors of faulting are differentiated vertical movements of the blocks comprising the platform. Such vertical movements might have been related to displacements of brine volumes. In the Late Cenozoic basins, movements along separate faults took place in the Late Pleistocene – Holocene.